Reconstruction of the Dirac-Type Integro-Differential Operator From Nodal Data. (18th August 2018) - Keskin, Baki; Dilara Tel, H.
Abstract: The inverse nodal problem for Dirac type integro-differential operator with the spectral parameter in the boundary conditions is studied. We prove that dense subset of the nodal points determines the coefficients of differential part of operator and gives partial information for integral part of it.